The Challenges of learning Kurdish for Kurds living in Sheffield/UK. (Journal of the College of Basic Education, 2026)
The purpose of this research is to explore the experiences and difficulties that Kurds living in the United Kingdom (UK) face when trying to learn Kurdish language. An online questionnaire is utilized to gather the data. Regarding the participant, Any Kurdish who is 12 years and over and a resident in the UK can participate. The researcher believe that this project will give a valuable insight into the experiences of language-learning for Kurds who live in the diaspora (outside of the Kurdish regions of Iraq, Iran, Syria, Turkey, Armenia and Azerbaijan) We are interested in exploring the issues, difficulties and factors which contribute to either a generally positive or negative experience of learning Kurdish. The aim of this research is to analyze students‟ perception for learning Kurdish language in terms of different variances. This studying is made in Nergiz Kurdish school in Sheffield/UK. the students in the school who born in UK whilst their mother tongue is Kurdish but they need to improve their Kurdish language.